2014
DOI: 10.1097/mcp.0000000000000035
|View full text |Cite
|
Sign up to set email alerts
|

Man-made mineral fibers and interstitial lung diseases

Abstract: OPINION Man-made mineral fibers and interstitial lung diseases Elizabeth FiremanPurpose of review Manufactured (artificial) fibers represent an important and continuously growing volume among substitutes to natural fibers. A major proportion of the population in an industrialized society has been, is, or will be in contact with these fibers. The fibrous configuration of asbestos is well recognized as being an important parameter in toxicity, and now that of synthetic fibers is also suspected of inducing seriou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 23 publications
0
7
0
4
Order By: Relevance
“…Respirable fibers of RCFs, particularly those exceeding the diameter of pulmonary macrophage (14 to 21 μm), could result in macrophage impairment and other lung irritation [ 6 ]. Epidemiological studies revealed that occupational exposure to RCFs may increase the incidence rate of respiratory symptoms, respiratory dysfunction, and pleural plaques [ 1 , 7 ]. In 1988 and 2002, the International Agency for Research on Cancer (IARC) classified RCFs as a 2B carcinogen (possibly carcinogenic to humans) twice based on sufficient animal studies and limited epidemiological data [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Respirable fibers of RCFs, particularly those exceeding the diameter of pulmonary macrophage (14 to 21 μm), could result in macrophage impairment and other lung irritation [ 6 ]. Epidemiological studies revealed that occupational exposure to RCFs may increase the incidence rate of respiratory symptoms, respiratory dysfunction, and pleural plaques [ 1 , 7 ]. In 1988 and 2002, the International Agency for Research on Cancer (IARC) classified RCFs as a 2B carcinogen (possibly carcinogenic to humans) twice based on sufficient animal studies and limited epidemiological data [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…We found a strong association between exposure to fiberglass and repetitive chest infections, and there was also a clinically important association between mineral fibers and chest infections, albeit the association was not statistically significant. Several articles have described potential health effects of mineral fibers [ 23 , 45 , 46 , 47 ]; however, only a handful number of reports clearly described its relationship with chest infections [ 48 ]. It has been observed that development of pneumonia among workers with a history of mineral fiber exposure could be a direct consequence of such exposure [ 31 ], as these fibers impart detrimental effects on the natural functioning of the airway macrophages [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, apart from the only available safety data sheet from the National Institute of Occupational Safety and Health (NIOSH) [ 19 ], information on health-related issues due to occupational exposure to aerogels is not available. Among other MMVFs, mineral fibers and refractory ceramic fibers have been identified as potential respiratory hazards, and their inhalation may lead to pulmonary carcinoma [ 20 ], adverse pleural conditions [ 21 , 22 ], and to some extent, interstitial changes in the lungs [ 23 ]. However, whether these MMVFs are associated with any chronic respiratory illnesses has not been systematically investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Fiberglass, sometimes also referred to as man-made vitreous fibers (MMVF), is a known respiratory, skin and eye irritant and an asthmagen [1]. In occupational settings, fiberglass exposure has been found to correlate with recurrent chest infections and pulmonary fibrosis [2,3]. Fiberglass fibers can vary in diameter, length, and chemical composition, but are predominantly amorphous (non-crystalline) mixtures of oxides of silicon, calcium, and other metals.…”
Section: Introductionmentioning
confidence: 99%